Загальна характеристика античного поселення Вікторівка-І - Бондаренко, Д. (Краєзнавство, 2018)
Стаття присвячена матеріалам досліджень Вікторівки-І – двошарової античної пам'ятки хори
Ольвії, що існувала на західному кордоні полісу на правому березі Березанського лиману. Планіграфічно
розділена на дві частини: південну займало поселення з житловою та господарською забудовою, північну –
святилище, що складалося з ритуальних зольників-жертовників. Встановлено два етапи функціонуван-
ня пам'ятки: перша половина VI – перша третина V ст. до н.е. та остання третина ІV – перша половина
ІІІ ст. до н.е. Серед досліджених об'єктів поселення до першого періоду відносяться житлові напівземлянки
та господарські комплекси. Другий період представлений залишками наземної сирцево-кам'яної будівлі. Archaeological complex Viktorovka-I is a two-layered ancient monument of the choir of Olvia, which existed
on the western outskirts of the policy on the right bank of the Berezanskiyi Estuary. Planigraphicaly, the monument
is divided into two parts: the southern part was occupied by a settlement with residential and economic
buildings; the northern one is a sanctuary consisting of ritual ash-altars.
This article is devoted to the characterization of the settlement alone and does not affect the materials for the
study of the sanctuary.
Today, two stages of the functioning of the settlement have been established: the first half of the VI is the first
third of the 5th century BC and the last third of the IV is the first half of the III century BC
From the disclosed objects, the first period includes residential, semi-dugouts and economic complexes,
grouped into at least three housing and utility modules.
The second period is represented by the remnants of a land-based raw stone building at Lower Steppe lands,
probably representing the type of a single collective manor of Hellenistic.
Based on the analysis of architectural remains and accompanying items of material culture, the article gives
an overall description of the improvement of the settlement and life of its inhabitants, farms, trades and crafts,
which the Hellenic colonists in the Viktrovsky settlement were engaged in designated epochs. Statistical analysis of
ceramics allows us to draw definite conclusions about the volumes of imports of different categories of goods in
Lower Steppe lands from the ancient centers of the Mediterranean and South Pontic, as well as to highlight some
export items. Статья посвящена материалам исследования Викторовки-I – двухслойного античного памятника
хоры Ольвии, существовавшего на западной окраине полиса на правом берегу Березанского лимана. Планиграфически разделен на две части: южную часть занимало поселение с жилой и хозяйственной застройкой, северную – святилище, состоящее из ритуальных зольников-жертвенников. Установлено два этапа функционирования памятника: первая половина VI – первая треть V вв. до н.э. и последняя треть
IV – первая половина III вв. до н.э. Из раскрытых объектов поселения к первому периоду относятся жилые полуземлянки и хозяйственные комплексы. Второй период представлен остатками наземной сырцово-каменной постройки.